The use of mobile phone apps by Australian gay and bisexual men to meet sex partners: an analysis of sex-seeking repertoires and risks for HIV and STIs using behavioural surveillance data. (19th April 2016) - Hull, Peter; Mao, Limin; Prestage, Garrett; Zablotska, Iryna; de Wit, John; Holt, Martin
Abstract : Background: Mobile phone apps are now the most popular method that Australian gay men use to find sex partners. Partner-seeking mobile phone apps use location functions to identify like-minded men and display their proximity. This study examines whether meeting partners via mobile apps is associated with a greater risk of HIV and sexually transmitted infections (STIs) than with other ways of meeting partners. Methods: Data were analysed from the Gay Community Periodic Surveys, community-based, cross-sectional surveys conducted in Australian state capital cities between 2010 and 2014. χ 2 tests and multinomial logistic regression were used to analyse differences in risk profiles of men who used different methods to meet partners. Results: Data were analysed from 36 428 men who participated in the Gay Community Periodic Surveys between 2010 and 2014. In 2014, 4116 men reported meeting sex partners with the use of mobile apps, increasing from 23.9% in 2011 to 42.5% in 2014. Men who used a combination of online and offline methods reported a greater number of sex partners and were more likely to report a recent STI than men who used online methods only or offline methods only. Conclusions: There has been a steep increase in the use of mobile phone apps by gay men in Australia to meet male partners. However, men who use a combination of mobile phone apps, internet websites and offline places to meet partners appear to be at increased risk of STIs or HIV compared with men who use a narrower range of online and offline methods.